Indústria 4.0: uma revisão sobre os requisitos mínimos para sua implementação em indústrias de processos - Chaguri, Lucas Ferreira (Universidade Federal de São Carlos, 2022)
The industrial sector has always faced great changes that were mainly marked by the great industrial revolutions. Each one of them brought new technologies, new production methods and great advances to the sector, in order to be able to serve the final customer more quickly and effectively. Currently, a new industrial revolution is taking place, a movement that started in Germany and was originally focused only on manufacturing, but which due to the rapid evolution of globalization and the IOT (The Internet of Things) is already taking over all the others. company sectors. This revolution is called Industry 4.0 and unlike other revolutions, this one does not just happen within the industry, but connects the entire value chain, up to the end customer, collecting and processing data from each step of the process and, through this information, promotes continuous improvements both in terms of production and customer experience. Therefore, the objective of this graduation work is to present what Industry 4.0 is and what are its main pillars, as well as to discuss the minimum level of maturity that a company needs to have in order to implement Industry 4.0 technologies, taking into account the infrastructure for the application of new technologies, the cultural transformation that must occur to meet the new needs and, finally, to present an assessment of the difficulties and challenges that a chemical industry faces to reach the minimum requirements necessary for the implementation of fourth-generation technologies generation.
Industry 4.0: a review of the minimum requirements for its implementation in process industries
Keywords: Revoluções industriais; Processos industriais; Cultura organizacional; Melhoria de processos; Lean manufacturing; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA